PELAKSANAAN PEMBINAAN PEGAWAI TATA USAHA DI SMP NURUL AMAL PALEMBANG - Izah Mukharomah; Febriyanti; Zulkipli (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study examines the implementation of administrative staff development at SMP Nurul Amal Palembang. The research problem arises from the fact that staff development has been carried out but has not yet achieved optimal results, as indicated by limited innovation, inconsistent discipline, and varying levels of competence among staff. The objective of this research is to analyze the implementation process of staff development and to identify supporting and inhibiting factors affecting its effectiveness. This study employs a qualitative approach with a case study design. Data were collected through in-depth interviews, observations, and documentation involving the principal, head of administration, and administrative staff. Data analysis was conducted through data reduction, data display, and conclusion drawing, while validity was ensured through source and method triangulation. The findings reveal that staff development has been implemented through directing, motivating, communicating, and coordinating activities, which generally contribute positively to improving work quality, responsibility, teamwork, and service ethics. Supporting factors include staff motivation, adequate facilities, and training opportunities, whereas inhibiting factors involve differences in educational background, work experience, and personal issues affecting performance. Overall, the implementation of staff development can be categorized as fairly effective, although strengthening in technological competence, innovation, and adaptive development strategies is still required to achieve more optimal administrative performance.